1994
DOI: 10.1002/actp.1994.010450110
|View full text |Cite
|
Sign up to set email alerts
|

Thermal graft copolymerization of 4‐vinyl pyridine onto ethyl cellulose in homogeneous media. 1. Influence of ammonium persulfate

Abstract: Graft copolymerization of 4-vinyl pyridine(4-VP) onto ethyl cellulose (EC) using ammonium persulfate (APS) as free radical initiator was studied in the toluene: DMSO (4:l v/v) solvent system. The weight conversion, grafting percentage and grafting efficiency were determined as functions of the polymerization temperature and of the concentration of monomer, ethyl cellulose and initiator. The homopolymerization of 4-VP in the presence ofAPS was also investigated. The graft copolymers were characterized by thin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
(1 reference statement)
2
9
0
Order By: Relevance
“…The results indicate that WC % and GP % decrease with increasing PVA content, whereas GE % increases. Therefore the increase in PVA content is always accompanied by an increase in solution viscosity ie the motion of macromolecule is restricted, so decreasing the WC % and GP % grafting parameters 23…”
Section: Resultssupporting
confidence: 83%
“…The results indicate that WC % and GP % decrease with increasing PVA content, whereas GE % increases. Therefore the increase in PVA content is always accompanied by an increase in solution viscosity ie the motion of macromolecule is restricted, so decreasing the WC % and GP % grafting parameters 23…”
Section: Resultssupporting
confidence: 83%
“…In Egypt, women have access to family planning as part of public primary health care (Rabie et al 2013; Ali 2002), and women’s use of long-acting reversible contraceptive methods increased steadily between 1984 and 2000 (Giusti and Vignoli 2006; Ali 2002). However, in the midst of rising fertility, the Ministry of Health and Population has observed a shift from IUDs to oral contraceptive pills in clinics (Abdel-Razik 2012). There remains a need to further understand factors that may contribute to this shift in method choice.…”
Section: Introductionmentioning
confidence: 99%
“…There remains a need to further understand factors that may contribute to this shift in method choice. Barriers to contraceptive use in Egypt include an absence of female physicians, a lack of physician training, son preference, region of residence, concerns about side effects, and husband’s disapproval (Giusti and Vignoli 2006; Ali 2002; Abdel-Razik 2012).…”
Section: Introductionmentioning
confidence: 99%
“…19 -21 Therefore, grafting of cellulose in such homogeneous systems possesses no complexities. [22][23][24] During the past few years, work on homogeneous grafting of vinyl monomers onto cellulose and some cellulose derivatives dissolved in nondegrading solvent systems such as DMSO/PF 24 -27 and DMSO/ PhMe 28,29 have been tried using different initiators [e.g., ammonium persulfate (APS), potassium persulfate (KPS), azobisisobutyronitrile (AIBN), and benzoyl peroxide (BPO)] but so far, work on homogeneous graft copolymerization of high ␣-cellulose dissolved in a DMAc/LiCl solvent system has not been investigated. It is reported that cellulose can be dissolved in a high concentration up to 16% in solvent systems such as DMAc/LiCl and N-methyl-2,2-pyrolidine/ lithium chloride (NMP/LiCl) without degradation of the polymer chain.…”
Section: Introductionmentioning
confidence: 99%